BaB4O5F4 with reversible phase transition featuring unprecedented fundamental building blocks of [B16O21F16] in the α-phase and [B4O6F4] in the β-phase. Issue 34 (30th March 2021) - Zhang, Wenbin; Guo, Siru; Han, Shujuan; Wang, Liying; Zhou, Xin; Yang, Zhihua; Pan, Shilie
Abstract : The first fluorooxoborate with reversible phase transition, BaB4 O5 F4 with a large band gap and moderate birefringence, features the unprecedented fundamental building blocks of [B16 O21 F16 ] in the α -phase and [B4 O6 F4 ] in the β -phase. Abstract : The first fluorooxoborate with reversible phase transition, BaB4 O5 F4, has been obtained. Interestingly, the two polymorphs, α - and β -BaB4 O5 F4 with rare [BOF3 ], feature various one-dimensional chains composed of the unprecedented fundamental building blocks of [B16 O21 F16 ] and [B4 O6 F4 ], respectively. First-principles calculations were performed to elucidate the structure–property relationships.